Counting Victories or Years? The Curious Case of the Sinopean Victory List - Ching-Yuan Wu (The 152nd AIA and SCS Joint Annual Meeting, 2021)
This paper examines a Sinopean victory list of the boxer Marcus Iutius Marcianus Rufus (French 2004: 76-77 no. 105) and the implications of counting the number of victories he won. Inscribed and set up by the Sinopean boule, the list represents an official recognition of the athlete's successful boxing career, which not only included victories in the four periodoi of mainland Greece, but also the Capitoline and Neapolitan games in Italy. The text has been studied by Theodoré Reinach (1916), George Bean (1953), and David French (2004), and resulting in different ways to count Rufus' victories.The three epigraphists encountered several issues with counting Rufus' victories. How to differentiate between a Bithynian koinon event from a metropolitan event held by Nicaea and Nicomedia is one issue, and whether to count the half-talent victories with the iselastic victories so to fit an ideal number of total victories that Rufus won is another, with the three epigraphists producing different solutions. Perhaps more perplexing of all, however, is how to interpret the Greek letters ΡΝ placed at the end of the victory list. Reinach interpreted them as the remaining letters of ἀνδριατί or "jeux mineurs" (Reinach 1916: 358). Bean and French saw them as Greek numerals, indicating the total tally of all listed victories. While the total tally seems a convincing interpretation on formulaic grounds, the arithmetic does not add up. On the one hand, tabulation indicates that Bean's count of total victories yields 159, with 110 half-talent victories and 49 iselastic victories. He reconciled the number by claiming to have seen signs of reinscribing in the squeeze, and suggested that Rufus initially won 101 half-talent victories, only to have achieved 110 at a later time, upon which occasion an update was applied to his monument (Bean 1953: 176). On the other hand, while French counted the half-talent victories as 110, and his total number of iselastic victories amount to 48, he still maintained that ΡΝ stands for "(In all) 150 victories," leaving the arithmetic issue open for further examination (French 2004: 77).This paper surveys other victory lists to study how koinon and metropolitan victories were differentiated and counted, and how chronographic features were positioned and identified. This paper also proposes to disassociate the number 150 from the total count of victories, and reconsider what was signified by this number. One possibility is the era: the 150th year of the era of Sinope. It has been demonstrated that Sinopean coinage during the imperial period used first the colonial era from 45 BCE, then the so-called Lucullan era of 70 BCE (Leschhorn 1993: 161-162). While era-based chronography is not found on extant imperial period inscriptions from Sinope, Rufus' victory list may be the first surviving example.